The chlamydial functional homolog of KsgA confers kasugamycin sensitivity to Chlamydia trachomatis and impacts bacterial fitness - Binet, Rachel (BioMed Central, 2009)
BACKGROUND: rRNA adenine dimethyltransferases, represented by the Escherichia coli KsgA protein, are highly conserved phylogenetically and are generally not essential for growth. They are responsible for the post-transcriptional transfer of two methyl groups to two universally conserved adenosines located near the 3'end of the small subunit rRNA and participate in ribosome maturation. All sequenced genomes of Chlamydia reveal a ksgA homolog in each species, including C. trachomatis. Yet absence of a S-adenosyl-methionine synthetase in Chlamydia, the conserved enzyme involved in the synthesis of the methyl donor S-adenosyl-L-methionine, raises a doubt concerning the activity of the KsgA homolog in these organisms. RESULTS: Lack of the dimethylated adenosines following ksgA inactivation confers resistance to kasugamycin (KSM) in E. coli. Expression of the C. trachomatis L2 KsgA ortholog restored KSM sensitivity to the E. coli ksgA mutant, suggesting that the chlamydial KsgA homolog has specific rRNA dimethylase activity. C. trachomatis growth was sensitive to KSM and we were able to isolate a KSM resistant mutant of C. trachomatis containing a frameshift mutation in ksgA, which led to the formation of a shorter protein with no activity. Growth of the C. trachomatis ksgA mutant was negatively affected in cell culture highlighting the importance of the methylase in the development of these obligate intracellular and as yet genetically intractable pathogens. CONCLUSION: The presence of a functional rRNA dimethylase enzyme belonging to the KsgA family in Chlamydia presents an excellent chemotherapeutic target with real potential. It also confirms the existence of S-adenosyl-methionine - dependent methylation reactions in Chlamydia raising the question of how these organisms acquire this cofactor.